PERILAKU LESBIAN DALAM NORMATIVITAS HADIS - miski, miski (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2016)
This article aims to explore the ?adîth thematically on the act of lesbianism in the normative roots. The methods used are operationally by generating ?adîths that are related to the topic, making typology, defining the primary ?adîth, takhrîj, and analyzing it in textual and contextual perspective. This article finds that some ?adîth which are talking straightly on lesbianism are narrated by al-?abrânî. It suggests that the act of lesbianism is a sinful deeds that are similar to the act of sexual intercourse (zinâ). In the wide analysis, it can be noted that Islam does not give space for making it legal for the doers of lesbianism. It is not only because the act of lesbianism has been considered as deviation from the nature of human sexual orientation, but also because it certainly contradicts to the basic legal of human relation. Otherwise, there are ample of ? adîth giving instruction to prevent people from such action, that is by not to open and look at other human genitals (?awrat), not to have body contact  that arouse sexual desire, and to emerge awarness of sexual identity and sexs by not to follow the deeds or dressing the opposite gender clothes.